Disseminated histiocytic sarcoma in an English springer spaniel presenting as primary cardiac disease. Issue 1 (25th February 2014) - Cobb, Malcolm; Ingram, Babs; Brower, Alexandra
Abstract : A four‐year‐old female English springer spaniel presented following an episode of weakness at home. On examination, the heart rate was very rapid and irregular, the pulses weak, and there were pulse deficits. An ECG showed a wide complex tachycardia, and echocardiography showed eccentric left ventricular dilatation and poor systolic function, serum troponin level was elevated. A presumptive diagnosis of myocarditis or dilated cardiomyopathy was made and the dog had a good initial response to treatment with mexiletine and later sotalol. Fifteen weeks later the dog developed respiratory difficulty, and a diffuse, nodular, interstitial lung pattern was evident throughout the lung fields on thoracic radiographs, and the owners elected to have the dog euthanased. On postmortem examination, a diagnosis of disseminated histiocytic sarcoma was made, with lesions found most extensively in the heart. Infiltrative myocardial disease should be considered as a potential diagnosis in patients with unexplained structural cardiac disease.